The Role of Parents at Home in Online Learning in Elementary Schools - Satriani DH (International Journal of Artificial Intelligence Research, 2022)
The online learning method is considered closer to the current generation of students who are known to be very integrated with technology products. This study has the objective of describing the role of parents in guiding students at home along with the obstacles faced by parents during online learning UPT SD Negeri 220, Bone Regency. This study used descriptive qualitative methods at UPT SD Negeri 220 Cinnong, Sibulue District, Bone Regency. Research subjectparents of students at SDN 220 Cinnong, Sibulue District, Bone Regency totaling 6 people. Interview and questionnaire data collection techniques. Data analysis was performed withdata reduction, data presentation and conclusion. The results of the study found that parents play an important role as motivators and facilitators who provide facilities for children in learning such as cellphones and internet cities, as well as support for children to continue to follow the learning process at school through online well. The obstacles experienced by parents are that they cannot always accompany their children to study at home and children have to take part in learning on their own without assistance from their parents.